A study protocol for a randomised controlled trial evaluating the use of information communication technology (WhatsApp/WeChat) to deliver brief motivational interviewing (i-BMI) in promoting smoking cessation among smokers with chronic diseases - William Ho Cheung Li (BMC Public Health, 2019)
Abstract Background The recent development of smoking cessation interventions for smokers with chronic diseases has focused heavily on brief interventions. However, these interventions are too brief to make an impact on these smokers, especially when most of them are without any intention to quit. Previous studies showed that smokers who did not want to quit might be interested in changing other health behaviours. Also, once people engage in a health behaviour, they are found more likely to change other unhealthy habits. Hence, a general health promotion approach could be a feasible approach to motivate smokers who do not want to quit to first engage in any desirable health behaviour, and later quit smoking when they intend to do so. This study aims to determine the potential efficacy and effect size of such intervention approach in promoting smoking cessation for smokers with chronic diseases. Methods This is a randomized controlled trial. A convenience sample of 60 smokers with chronic diseases will be randomly assigned into either experimental (n = 30) or control group (n = 30). Smokers in the experimental group will receive an individual face-to-face brief motivational interviewing (MI) with generic advice on selected health behaviour. More brief MI messages will be delivered to them via WhatsApp/WeChat for 6 months. For subject in the control group, they will be asked to indicate their desirable health-related practice. However, no MI and booster interventions will be given. All subjects will complete a questionnaire at 1, 3, 6 and 12 months. Subjects abstinent from cigarettes at 12 months will perform a biochemical validation. The primary outcome is biochemically validated smoking abstinence at 12 months. Effect size of the intervention will be estimated by the odd ratios using intention-to-treat. Discussion This is the first study to determine the potential efficacy for the use of a personalized general health promotion approach in promoting smoking cessation for smokers with chronic diseases. If our proposed intervention is effective, we will able to assist smokers with chronic disease to quit smoking and change their health behaviour simultaneously. Trial registration CinicalTrials.gov NCT03983330 (Prospectively registered), registered on June 12, 2019.